2020
DOI: 10.3390/agronomy10030435
|View full text |Cite
|
Sign up to set email alerts
|

Legume Biofortification and the Role of Plant Growth-Promoting Bacteria in a Sustainable Agricultural Era

Abstract: World population growth, together with climate changes and increased hidden hunger, bring an urgent need for finding sustainable and eco-friendly agricultural approaches to improve crop yield and nutritional value. The existing methodologies for enhancing the concentration of bioavailable micronutrients in edible crop tissues (i.e., biofortification), including some agronomic strategies, conventional plant breeding, and genetic engineering, have not always been successful. In recent years, the use of plant gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 100 publications
0
16
0
1
Order By: Relevance
“…More refined estimates of human nutrition consider different aspects, such protein quality via, for example, the amino acid profile (Leinonen et al, 2019), or other bioavailable micronutrients (which may be enhanced by cultivation and biofortification strategies). Biofortification can be achieved through different methods, such as conventional plant breeding, genetic engineering, agronomics tactics, and more recently plant growth-promoting bacteria (PGPB) strategies (Roriz et al, 2020). The latter, for instance, improves crop yields and also iron availability for human diets (an aspect not assessed in this study).…”
Section: Assessing Sustainable Human Nutritionmentioning
confidence: 99%
“…More refined estimates of human nutrition consider different aspects, such protein quality via, for example, the amino acid profile (Leinonen et al, 2019), or other bioavailable micronutrients (which may be enhanced by cultivation and biofortification strategies). Biofortification can be achieved through different methods, such as conventional plant breeding, genetic engineering, agronomics tactics, and more recently plant growth-promoting bacteria (PGPB) strategies (Roriz et al, 2020). The latter, for instance, improves crop yields and also iron availability for human diets (an aspect not assessed in this study).…”
Section: Assessing Sustainable Human Nutritionmentioning
confidence: 99%
“…The strong affinity of microbial siderophores for Fe allows them to compete with plants by 'stealing' Fe from low-affinity phytosiderophores [33,45,47]. Despite this capability, numerous studies demonstrated a beneficial relationship between the presence of PGPMs and Fe accumulation by plants [43,[48][49][50].…”
Section: Fe Mobilization By Microbesmentioning
confidence: 99%
“…Microbial biofortification of Fe in plants can occur via several mechanisms: the presence of PGPMs can induce increased root hair proliferation and branching, trigger plant biochemical responses to Fe limitation, and prevent Fe acquisition by phytopathogenic microbes [43,[48][49][50]. In addition, there is also considerable evidence that plants can utilise microbial siderophores, which appear to be dictated by the plants' Fe acquisition strategies.…”
Section: Fe Mobilization By Microbesmentioning
confidence: 99%
“…400 kg N ha -1 [85][86][87]. Legumes improve soil quality, enhance C and N cycling, and reduce pollution [88][89][90][91], [Crop diversification]). They are therefore environmentally more sustainable than using external mineral or animalderived fertiliser inputs [36], especially where forage legumes and inter-cropping are used ([Crop diversification], [92,93]).…”
Section: Soil Carbon and Nutrient Supplymentioning
confidence: 99%